Cardio-renal mechanisms of adaptation in normal and with heart failure - A. I. Gozhenko; S. V. Biletskiy; A. V. Bobilev (Kazimierz Wielki University, 2018)
The pathogenesis of chronic heart failure (CHF) is a complex multifactorial process, which is a close combination of manifestations of the effects on the cardiovascular system of the etiological factor (s) and the mobilization of a whole complex of compensatory mechanisms [30]. According to the first conceptual models (cardiac (1950s) and cardiorenal (1960s)) pathogenesis, the main role in the formation of CHF belonged to a decrease in cardiac contractility (systolic dysfunction), as well as electrolyte retention and body water. [4, 14, 39]. The aim of the study was to study the role of the renin-angiotensin-aldosterone system and the natriuretic hormone in adaptive changes in water-salt homeostasis with an increase in venous blood return to the heart in healthy and in patients with stable ischemic heart disease with chronic heart failure stage I (stage I). The results of the study concluded: - in healthy individuals, an increase in venous return of blood to the heart (preload) in anti-orthostasis on the background of 0.5% water load is accompanied by adaptive changes in cardiohemodynamics, volemic homeostasis and neurohumoral regulation of water-salt metabolism, manifested by an increased influence of the parasympathetic department ANS, a decrease in heart rate, an increase in ASI while maintaining the IOC at the same level, an increase in diuresis, a decrease in the activity of the RAAS, an increase in the content of α-PNOG; - in patients with coronary artery disease with HNK I st. with an increase in preload at the 30th minute of anti-orthostasis, changes in cardio hemodynamics (decrease in IOC) and cardiac rhythmograms were revealed, indicating a depletion of myocardial reserve capacity and vegetative regulation of heart rhythm. The lack of heart rate dynamics and cardiac rhythmograms in anti-orthostasis reflects an increase in the activity of the sympathetic section of the autonomic nervous system in patients with coronary artery disease with the initial stage of HNK; - kidney reaction to anti-orthostasis and 0.5% water load in patients with coronary artery disease with HNK, I st. expressed in increased diuresis in the absence of changes in the activity of the RAAS, which indicates the predominance of antinatriuretic systems over natriuretic; - the earliest indicator of the development of heart failure in patients with coronary artery disease is sodium retention, aimed at increasing the BCC, venous return of blood to the heart and stimulation of the heterometric mechanism of Frank-Starling.